Mexico and International Anti-corruption Conventions - Solís - Barrios , Michel Antonio; Cárdenas - Cárdenas, Gilberto (Universidad Francisco de Paula Santander, 2024)
This article analyzes Mexico's compliance with its international commitments under the Inter-American Convention Against Corruption, the Convention on Combating Bribery of Foreign Public Officials and the United Nations Convention Against Corruption. In order to achieve the proposed objective, the research is divided into four sections: first, the concept of corruption is discussed beyond a simplistic term that only includes crimes that are part of acts of corruption; second, the international conventions are analyzed as instruments of global governance; third, the conventions ratified by Mexico in its fight against corruption are identified; and finally, an analysis is made of the measures designed by Mexico to combat corruption at the national level based on the instruments of international cooperation. As conclusion, it can be stated that Mexico has complied with the commitments acquired in the three international conventions, at least at the legal level; however, the problem is centered on the lack of effective supervision of the measures adopted.